2018
DOI: 10.17531/ein.2018.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of Ti6Al4V alloy coated with caprolactone-based biodegradable polymeric coatings

Abstract: The aim of this study was to determine the influence of long-term exposure of Ringer’s solution on degradation of the anodically oxidated Ti6Al4V alloy coated with a biodegradable polymer coating. Polymeric coatings made of poly(glycolide-ε-caprolactone) – G-Cap and poly(glycolide- ε-caprolactone-lactide) – G-Cap-L were applied by a dip-coating method. Degradation was assessed on the basis of the results of pitting corrosion resistance and density of metal ions infiltrating to the solution. Studies were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…This remodelling indicates the progressive degradation of the polymer coatings, and thus the increasing contact of the metal substrate with the surrounding corrosive environment. The effectiveness of limiting the degradation of the metal substrate by polymer coatings has been confirmed in studies of the concentration of ions releasing into Ringer's solution [9]. Compared to the concentration of metal ions permeating the substrate in the case of polymer coatings regardless of their type as well as the method of obtaining, a reduction in the number of ions was observed (Table 4).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This remodelling indicates the progressive degradation of the polymer coatings, and thus the increasing contact of the metal substrate with the surrounding corrosive environment. The effectiveness of limiting the degradation of the metal substrate by polymer coatings has been confirmed in studies of the concentration of ions releasing into Ringer's solution [9]. Compared to the concentration of metal ions permeating the substrate in the case of polymer coatings regardless of their type as well as the method of obtaining, a reduction in the number of ions was observed (Table 4).…”
Section: Discussionmentioning
confidence: 81%
“…6). Moreover, in the 1.5 to 2 V potential range for the samples after 1, 2 and 3-month exposure, a distinct increase in the current density was observed [9]. The increase in current density in this potential range is related to the remodelling of the oxide layer on the surface of the Ti alloy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This proved that the applied polymer coatings constituted a protective barrier that limited the release of the degradation products of the metal substrate into the Ringer's solution. Preliminary studies of the authors showed a beneficial effect of reducing the mass density of metal ions by biodegradable polymer coatings, which were applied on stainless steel Ti6Al4V and Ti6Al7Nb alloys; however, the applied surface treatment parameters were different than the ones used in the present study [39,47,48]. In the previous work, concerning the PLGA coating (10% w/w) [48], the influence of the number of dips in the process of applying polymer coatings on the mass density of ions releasing into the solution was also observed.…”
Section: Biological Test Resultsmentioning
confidence: 99%
“…In the field of orthopedics and in dental prosthetics, titanium found a wide range of applications [ 6 , 7 ]. Its high corrosion resistance is attributed to passive layers consisting of amorphous TiO 2 , formed on the surfaces [ 8 , 9 , 10 ]. It may be characterized as a very difficult-to-cut material due to its endurance and relative elongation (6–15%).…”
Section: Introductionmentioning
confidence: 99%